2021
DOI: 10.4085/1062-6050-0708.20
|View full text |Cite
|
Sign up to set email alerts
|

Impact Sound Across Rearfoot, Midfoot, and Forefoot Strike During Overground Running

Abstract: Context: There are three common foot strike techniques in runners. Whether these techniques generate different sounds at the point of impact with the ground may influence lower limb kinetics. No previous studies have determined whether such relationships exist. Objectives: To determine foot-ground impact sound characteristics and to compare the impact sound characteristics across foot strike techniques and the relationships between impact sound characteristics and vertical loading rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Another possibility is that the heel prevented an excessive temperature elevation by dissipating a portion of the collisional net-negative work as sound. While this seems unlikely based on a prior study ( Hung Au et al, 2021 ), a direct measurement of sound is needed to verify or refute sound as a dissipation mechanism. An additional possibility is that the motion of the feet in the air, especially during the swing phase, could produce a cooling effect ( Burton, 1934 ; Chang et al, 1987 ; Melnikov et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is that the heel prevented an excessive temperature elevation by dissipating a portion of the collisional net-negative work as sound. While this seems unlikely based on a prior study ( Hung Au et al, 2021 ), a direct measurement of sound is needed to verify or refute sound as a dissipation mechanism. An additional possibility is that the motion of the feet in the air, especially during the swing phase, could produce a cooling effect ( Burton, 1934 ; Chang et al, 1987 ; Melnikov et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, principles of acoustics suggest that the amplitude of the produced sound should be proportional to the amplitude of the impact pressure. However, Hung Au et al, 2021 reported a statistically non-significant association between impact sound amplitude and vertical impact rate during running, with heel-strike running having the lowest peak sound amplitude ( Hung Au et al, 2021 ). Thus, although energy dissipation as sound is plausible, it seems reasonable to predict that the heel’s collision energy during walking may be dissipated as heat.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Greater instantaneous impact loading may generate louder sounds of footsteps, which have been previously shown to be moderately correlated to vertical loading rates and peak propulsion forces [12,13]. The sounds of footsteps have been used in gait retraining to reduce instantaneous impact loading during running [7,14] and can be used to classify different running styles [15]. Moreover, muscle fatigue increases the loading rate [16,17], which can be strongly correlated with increases in peak footstep sounds in fatiguing conditions [13].…”
Section: Introductionmentioning
confidence: 99%